Structural and meaningful organization of coach's attitudes in the formation of operational thinking in young athletes - Kim, T.K.; Kuzmenko, G.A.; Rodkina, I.I.; Fedorov, A.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to specify the content of the coach's attitudes to the young athlete with a focus on the development and full-fledged demonstration of operational thinking at a high pace of training activities. Methods and structure of the study. In the course of scientific work, the following research methods were used: analysis of literary sources; content analysis of the trainer's attitudes; testing: psychomotor abilities, differentiation ability, cognitive functions, styles of activity, components of personality orientation. The study was conducted on the basis of the Chertanovo Sports Boarding School, Olympic Reserve Sports School No. 1, and the Moscow National Hockey Center in April 2021 with the participation of 10 coaches and 34 young athletes. Results and conclusions. The factors revealed in the course of the study, reflecting the activity features of the implementation of operational thinking at a high pace of execution of a motor task in young athletes-players (“the number of precise, prompt actions in the format of the type of thinking”; “the ability to differentiate the parameters of actions with a constant concentration of sensory-perceptual attention” ; "quantitative and temporal characteristics of activity"; "the number of correct decisions in a changing environment") made it possible to specify the coach's instructions for young athletes in the direction of development and full realization of the ability to operational thinking in conditions of a high pace of training and competitive activity.